2013
DOI: 10.1108/cwis-07-2013-0029
|View full text |Cite
|
Sign up to set email alerts
|

Toward a learner-centered system for adult learning

Abstract: Purpose -The purpose of this paper is to present an e-learning system that integrates the use of concepts of virtual learning environments, personal learning environments, and social network sites. The system is based on a learning model which comprises and integrates three learning contexts for the adult learner: the formal, instructional context, the personal context for learning management, and the social peer context. The paper outlines how the Open University of the Netherlands (OUN) implemented this mode… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 16 publications
1
6
0
Order By: Relevance
“…The new e-learning system was founded on the concept of learning networks (Koper, 2009): a technology-supported community of people in a particular discipline who are helping each other to better understand and handle certain events and concepts in work or life. The system aimed at improving the learner's user experience and accessibility by integrating formal learning, social learning and personal learning into one system (Hermans, Kalz, & Koper, 2014). Moreover, from a business point of view, it was much more efficient to serve different target groups through one single system instead of maintaining a cluster of dedicated e-learning systems for separate learner groups.…”
Section: A New Business Model and Implications For Authoring And Delimentioning
confidence: 99%
“…The new e-learning system was founded on the concept of learning networks (Koper, 2009): a technology-supported community of people in a particular discipline who are helping each other to better understand and handle certain events and concepts in work or life. The system aimed at improving the learner's user experience and accessibility by integrating formal learning, social learning and personal learning into one system (Hermans, Kalz, & Koper, 2014). Moreover, from a business point of view, it was much more efficient to serve different target groups through one single system instead of maintaining a cluster of dedicated e-learning systems for separate learner groups.…”
Section: A New Business Model and Implications For Authoring And Delimentioning
confidence: 99%
“…(2019) found that PR improved the task accuracy of the learners because it eliminated the intention of escaping from the tasks. These three elements, the discipline of learners, active learning environment and self-motivation of learners, are the three catalysts of implementing LCP in an ODL environment revealed by Hermans et al. (2013).…”
Section: Positive Reinforcement and Scaffoldingmentioning
confidence: 99%
“…New demands on universities for user-centred education (Hermans, Kalz & Koper, 2013) has resulted in universities offering more than just brick-and-mortar education, and embracing distance education and the subsequent emergence of multi or dual-mode education (Osei et al, 2013). In response to these developments, academic libraries in multi-mode universities are expected to provide equitable services to its increasingly divergent constituency including distance learners (ACRL, 2008).…”
Section: Introductionmentioning
confidence: 99%